2014
DOI: 10.1589/jpts.26.1313
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Tap Water and Normal Saline Iontophoresis in Idiopathic Hyperhidrosis: A Case Report

Abstract: [Purpose] The purpose of this study was to evaluate the efficacy of tap water (drinking water) and normal saline (sodium chloride solution 0.9%) iontophoresis treatment for a patient with idiopathic hyperhidrosis [Subjects and Methods] In this study, tap water and normal saline iontophoresis were used to treat a 21 year-old female who was suffering from severe palmoplantar idiopathic hyperhidrosis. Post-iontophoresis sweat intensity of 8 treatment sessions were averaged and then normalized relative to the corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
0
6
0
2
Order By: Relevance
“…However, there are controversies regarding the use of tap water as a standard solution, since tap water varies in its ionic constituents according to the locality. In a comparative study done by Yaghobi et al, 24 normal saline iontophoresis was found to be 1.7 times more effective than tap water iontophoresis at obstructing secretion in primary hyperhidrosis.…”
Section: Saline Water Iontophoresismentioning
confidence: 93%
“…However, there are controversies regarding the use of tap water as a standard solution, since tap water varies in its ionic constituents according to the locality. In a comparative study done by Yaghobi et al, 24 normal saline iontophoresis was found to be 1.7 times more effective than tap water iontophoresis at obstructing secretion in primary hyperhidrosis.…”
Section: Saline Water Iontophoresismentioning
confidence: 93%
“…Tap water can be replaced by aluminum chloride, anticholinergic agents, or botulinum toxin to achieve better results. Saline proved to be more effective than tap water in a study 56 . Patients who are pregnant, have metal implants, pacemakers or have epilepsy cannot take the treatment 18 .…”
Section: Device‐based Treatmentsmentioning
confidence: 98%
“…Saline proved to be more effective than tap water in a study. 56 Patients who are pregnant, have metal implants, pacemakers or have epilepsy cannot take the treatment. 18 Transient vesiculation, redness, paresthesia, and discomfort are the side effects.…”
Section: Iontophoresismentioning
confidence: 99%
“…The combined use of anticholinergic agents, such as poldine methylsulfate and glycopyrronium bromide, can increase the effectiveness of iontophoresis. [27][28][29][30][31]…”
Section: Iontophoresismentioning
confidence: 99%